2007
DOI: 10.1128/jvi.01496-07
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6A (HHV-6A) and HHV-6B Alter E2F1/Rb Pathways and E2F1 Localization and Cause Cell Cycle Arrest in Infected T Cells

Abstract: E2F transcription factors play pivotal roles in controlling the expression of genes involved in cell viability as well as genes involved in cell death. E2F1 is an important constituent of this protein family, which thus far contains eight members. The interaction of E2F1 with its major regulator, retinoblastoma protein (Rb), has been studied extensively in the past two decades, concentrating on the role of E2F1 in transcriptional regulation and the role of Rb in cell replication and cancer formation. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…(18,27). As shown here in HHV-6A infection of SupT1 T cells, there was pronounced up-regulation of E2F1 and DP1 proteins by 48 h.p.i.…”
Section: E2f1-dependent Transcription and Entry Into The S Phase (26)mentioning
confidence: 60%
See 2 more Smart Citations
“…(18,27). As shown here in HHV-6A infection of SupT1 T cells, there was pronounced up-regulation of E2F1 and DP1 proteins by 48 h.p.i.…”
Section: E2f1-dependent Transcription and Entry Into The S Phase (26)mentioning
confidence: 60%
“…It has been shown that human cytomegalovirus (HCMV) tegument protein pp71 induces Rb degradation (16) and that HCMV kinase protein UL97 phosphorylates Rb protein (17). We have shown (18) that the infection of SupT1 T cells with HHV-6A was associated with cellcycle arrest at the G2/M phase. Such arrest might be advantageous for viral replication and the production of the typical HHV-6 cytopathic effect, consisting of multiple fused infected cells.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The SupT1 CD4 ϩ human T cells (37) were obtained from the National Institutes of Health AIDS Research and Reference reagent program. The viruses were propagated in SupT1 cells as described before (38). The virus with the short DR is infectious both by cell-to-cell and cell-free propagation.…”
Section: Methodsmentioning
confidence: 99%
“…The isolates were propagated initially in activated PBLs and CBMCs and then in continuous T-cell lines, including HSB-2, J-JHAN, SupT1, Molt-3, and MT-4 (11,45). The U1102 strain isolated by Downing and colleagues (12) was contributed to our laboratory by Robert Honess and was propagated first in activated PBLs and CBMCs (11,18,36,45) and then in J-JHAN and SupT1 T cells (4,30). To answer the question with regard to the origin of the short DRs and their structure, we have compared earlier viral HHV-6A passages with the currently propagated virus and the HHV-6A BAC clones.…”
mentioning
confidence: 99%